Evidence for an ice shelf covering the central Arctic Ocean during the penultimate glaciation; Nature Communications; Vol. 7 - Jakobsson M. Martin; Nilsson J. Johan; Anderson L. Leif; Backman J. Jan; Bjork G. Goran; Cronin Th. M. Thomas; Kirchner N. Nina; Koshurnikov A. V. Andrey Viktorovich; Mayer L.; Noormets R. Riko; O'Regan M. Matthew; Stranne Ch. Christian; et al. (2016, 2016)
Title screen